Critical AC frequency for stable operation of electrowetting-driven optofluidic devices with polymeric electrolyte solutions - 박재범; 하종현; 최규환; 배정목; 김호영 (Journal of Mechanical Science and Technology, 2019)
EWOD (electrowetting on dielectric) is a viable scheme to drive optofluidic devices that utilize the liquid interface as a refractive surface. Although AC (alternating current) voltage is often applied to an electrode in EWOD devices to improve electrical characteristics, it may cause oscillations of liquid interfaces which can be detrimental to the system's performance as an optical device. Here we experimentally identify the origin of the interfacial oscillations of polymeric electrolyte solutions by observing the dynamic responses of contact lines as a function of the AC frequency. Penetration of small charged matters into the dielectric film of the opposite polarity is shown to induce the voltage relaxation that leads to deterioration of electrowetting performance. Measuring the relaxation time scale which is different for each polarity allows us to find the critical AC frequency that ensures stable interface control.
Keywords: Electrowetting-on-dielectric; Frequency; Interfacial oscillation; Polymeric electrolyte